The Potential Role of Hypochlorhydria in the Development of Duodenal Dysbiosis: A Preliminary Report - Filardo, Simone; Scalese, Giulia; Virili, Camilla; Pontone, Stefano; Di Pietro, Marisa; Covelli, Antonio; Bedetti, Giorgio; Marinelli, Paride; Bruno, Giovanni; Stramazzo, Ilaria; Centanni, Marco; Sessa, Rosa; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
In recent years, the role of gastric and duodenal microbiota has acquired increasing importance in the homeostasis of the host, although, to date, most evidence concern the faecal microbiota. Indeed, the gastric, and duodenal microbiota are challenging to study, due to gastric acid, bile, digestive enzymes, and rapid transit time. Specifically, the gastric acid environment may influence their bacterial composition since the acid barrier protects against orally ingested microorganisms and leads to their inactivation before reaching the intestine. The aim of this study was to assess a correlation between intragastric pH and gastric as well as intestinal microbiota of patients with histologic gastric alterations. pH was measured in the gastric juice and the bacterial composition in gastric and duodenal biopsies and faecal samples, was investigated via 16s rRNA gene sequencing. The main result is the direct correlation of duodenal microbiota biodiversity, via alpha diversity measures, with intragastric pH values. In particular, patients with hypochlorhydria showed increased duodenal microbiota biodiversity, higher intragastric pH values being prevalent in patients with chronic atrophic gastritis. Lastly, the latter was also strongly associated to the presence of oral bacteria, like Rothia mucilaginosa, Streptococcus salivarius and Granulicatella adiacens, in the duodenal microbiota. In conclusions, our results suggest a low-acid gastric environment as a contributive factor for duodenal dysbiosis, potentially leading to the development of pathological conditions of the gastrointestinal tract.